Implementation of Islamic Corporate Governance: A Case Study in BMT NUsantara UMAT MANDIRI Kalidawir Tulungangung - Ahmad Sodiq (Universitas Airlangga, 2017)
BMT NUsantara UMAT MANDIRI as financial institutions are expected to implement the corporate governance of Islam (Islamic Corporate Governance) that comply with Islamic principles. The implementation of Islamic Corporate Governance can increase consumer trust and confidence. The purposes of this research are to know about Islamic Corporate Governance as Islamic finance institutions and to know the application of Islamic Corporate Governance BMT NUsantara UMAT MANDIRI Kalidawir Tulungagung.